ʺSystem of professional competencies for future specialists in the chemical industryʺ - Lazarieva , T.; Shaposhnyk , A. (Problems of Engineer-Pedagogical Education, 2024)
The article is devoted to the theoretical justification and development of professional competencies for future specialists in the chemical industry. The relevance of the chosen topic is explained by the significant opportunities for modern chemical enterprises to implement advanced technologies, use unconventional raw materials and materials, modern equipment, and innovative approaches to technological production processes, including nanotechnologies. Attention is drawn to the ecological, economic, and social challenges that require innovative approaches and solutions. In this context, the formation of a system of professional competencies in future specialists of the chemical industry is considered as an important step to ensure the stability and successful development of the industry in the face of global challenges. The article explores the concept of "professional competence of a specialist in the chemical industry" as a set of necessary knowledge, skills, abilities, and personal qualities required for successful work in the chemical industry. The authors propose an approach to developing a system of professional competencies by defining qualification requirements and production functions for specialists in the chemical industry, including engineering and technical and medical-biological specialties. As a result of the analysis of production functions, a system of professional competencies for future specialists in the chemical industry has been developed, and the content of integral, general, and professional competencies has been specified. It has been established that integral competence involves a deep understanding of processes and technologies of chemical production and the ability to use creativity and an innovative approach to solving tasks. General competencies encompass aspects such as goal setting, motivation for achieving results, the ability to independently solve problems, and continuous self-development. Professional competencies include mastery of fundamental concepts and theories of chemistry, the ability to analyse chemical processes and technologies, use mathematical models and software for predicting substance properties, conducting chemical research and data analysis, quality control of products and production processes, mastery of risk assessment and minimization methodology in the chemical industry. The results of the research can be used to develop educational programs and train future specialists in the chemical industry, contributing to the improvement of the quality of education and the preparation of qualified personnel in this field.